Analisis Pengelolaan Barang Milik Daerah (BMD) Di Bakesbangpol Provinsi Riau - Indra Mardeni Putra; Adianto; Indry; Ayu Tri Utami (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2025)
This study aims to analyze the management of regional assets (BMD) in the Riau Province Bakesbangpol and identify challenges in these management activities. The research method used is descriptive qualitative with data collection techniques in the form of direct observation, documentation studies, and interviews with informants selected purposively. The data obtained were subjected to data reduction, data presentation, and verification processes to draw conclusions. This study found that the management of regional assets in Bakesbangpol has been carried out in accordance with the rules that should refer to theoretical aspects and regulations governing the cycle and stages of regional asset management, namely Permendagri No. 19 of 2016. The challenges faced by Bakesbangpol Riau Province in managing BMD lie in the administrative aspects during the transition or change of regional asset managers. In addition, the less than optimal utilization of information technology needs to be addressed so that BMD management can be carried out effectively and efficiently in the future